Telaah Pemicu Perkawinan Paksa di Stasi Santo Yosef Paroki Nikolaus Pacar Keuskupan Ruteng - Candra, Evaldus Rafiko; Japa, Hendrikus Balzano; Endi, Yohanes (Jurnal Masalah Pastoral, 2024)
The focus of this paper is an examination of the triggers of marriage in the St. Joseph Parish, Nikolaus Pacar, Diocese of Ruteng. Forced marriages in St. Joseph Parish, Nikolaus Pacar, reveal the complexities and challenges of preserving individual freedom and dignity. This phenomenon involves a variety of factors, including economics, debt, culture, pregnancy outside of marriage, arranged marriage and parental pressure. This research uses qualitative methods with interviews as data collection and elaborated with other sources that support the writing of this article. Forced marriages result in family conflict and unhappiness and an increase in domestic violence. Awareness of the importance of freedom in marriage is vital, as relationships built on coercion are at risk of disharmony and conflict. To ensure the success of a marriage, it is important that both partners have the freedom to make decisions. Conscious decisions will make the relationship harmonious. So in making decisions, open communication between the two people is needed.